2010
DOI: 10.1111/j.1447-0756.2009.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucocorticoid on brain acetylcholinesterase of developing chick embryos

Abstract: The cerebrum, cerebellum and optic lobe of chick embryos could be influenced by glucocorticoids because of the presence of glucocorticoid receptor mRNA. Although the effects observed after treatment with excess glucocorticoids (even no effects after mifepristone treatment) were transitory, they may alter the developmental program in ways that could result in lasting change and influence behavioral activities after hatching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Preparing and caring for fertilized eggs was carried out as previously described 18,19 . Fertilized white Leghorn chicken eggs were purchased from a local hatchery and placed in an incubator at approximately 12.00 hours on day 1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Preparing and caring for fertilized eggs was carried out as previously described 18,19 . Fertilized white Leghorn chicken eggs were purchased from a local hatchery and placed in an incubator at approximately 12.00 hours on day 1.…”
Section: Methodsmentioning
confidence: 99%
“…The wet weights were determined and the specimens were stored at −80°C until further use. AChE activities in the telencephalon, cerebellum and optic lobe were assayed by the method described in a previous paper 18 . Briefly, the supernatant obtained after the homogenates were centrifuged at 10 000 rpm for 5 min at 4°C was used to determine AChE activities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Expression is first detected in the embryonic rat brain, and levels are high and similar in the developing cerebellum and hippocampus (Lawson et al 1992). Prenatal glucocorticoids influence the development of Purkinje neurons (Rugerio-Vargas et al 2007) and a recent study using chick embryos has reported the presence of GR mRNA in the embryonic cerebellum (Yamate et al 2010). Furthermore, Yamate et al also showed that effects after treatment with excess glucocorticoids are mediated via GRs and indirectly influence behavioral activity after hatching.…”
Section: Adrenal Steroid Hormones and Cerebellar Developmentmentioning
confidence: 94%